Correct Answer - Option 3 : 5

__Concept:__

Let us consider the standard form of a quadratic equation, ax2 + bx + c =0

Let α and β be the two roots of the above quadratic equation.

The sum of the roots is given by: \({\rm{α }} + {\rm{β }} = - \frac{{\rm{b}}}{{\rm{a}}} = - \frac{{{\rm{coefficient\;of\;x}}}}{{{\rm{coefficient\;of\;}}{{\rm{x}}^2}}}\)

The product of the roots is given by: \({\rm{α β }} = \frac{{\rm{c}}}{{\rm{a}}} = \frac{{{\rm{constant\;term}}}}{{{\rm{coefficient\;of\;}}{{\rm{x}}^2}}}\)

__Calculation:__

Let the roots of 5x2 + 26x + k = 0 are α and β

Given α = 1/β

⇒ α.β = 1 ----(i)

Compare with general equation ax^{2} + bx + c = 0

a = 5, b = 26, c = k

According to the concept used

⇒ α.β = k/5 ----(ii)

From (i) and (ii), we get

k/5 = 1

**∴The value of k is 5.**